Automatic Data Downloading Program (DDP) in Determining Regional Ionosphere Model - Cevat İnal; Ömer Yıldırım; Sercan Bülbül; Fuat Başçiftçi (Journal of New Results in Science)
GNSS (Global Navigation Satellite System) signals passthrough various layers of the atmosphere until they reach the receiver on theEarth. One of these layers is the Ionosphere. Ionosphere may be defined as theatmospheric layer that consists of the gasses that are ionized with sunrayslocated 60 and 1100 km above the ground level with important effects on thesignals used by satellite-based positioning, short-wave communication, andother communication systems. One of the important parameters that express thecharacteristics of the Ionosphere is the Total Electron Content (TEC), which isa function of the electron density that shows variations with the radiation ofthe Sun. The TEC value cannot be obtained directly from GNSSmeasurements; however, it may be predicted with the combinations produced.In the scope of the present study, the Bernese v5.2 GNSS scientific Softwarethat was developed by the Swiss Bern University Astronomy Institute (AIUB) wasused in the determination of the TEC values for the Regional Ionosphere model.Before the stage in which the TEC values are determined with the Bernese v5.2GNSS Software, some files must be downloaded from the Internet in the Berneseformat according to GPS day/week and year/the day of year values and copies tothe DATAPOOL folder, which is created with the use of the software. For thispurpose, it has been ensured that the files in the Bernese format are obtainedfrom the relevant Internet addresses in an automatic manner by using a seriesof commands with the name Data Downloading Program (DDP) in the MATLAB for thepurpose of facilitating the manual data collection process and eliminatingother possible difficulties that might appear. The Regional TEC values arecomputed with the Bernese v5.2 GNSS Software by using the downloaded files.